Advances in Fluid Dynamics with Emphasis on Multiphase and Complex Flow - Hernández, S. (Santiago), 1951-; Vorobieff, Peter, 1967- (WIT transactions on engineering sciences ;, 2021)
Presented papers from the 11th International Conference on Advances in Fluid Dynamics with emphasis on Multiphase and Complex Flow are contained in this book and cover a wide range of topics, including basic formulations and their computer modelling as well as the relationship between experimental and analytical results.